BY-STANDER HONORIFIC EXPRESSION VIEWED WITHIN SOCIAL PHENOMENA AND TRANSLATION STUDIES - Mochamad Nuruz Zaman (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
Development of language areas, especially in terms of addresses, has not been widely studied by sociolinguistic researchers. This gap is strengthening this research to be integrated with translation aspect. Its application of qualitative research methods with a descriptive approach is carried out with data sources and data taken from Okky Madasari’s novel, which exposes a lot of the social live in various ways. Analyzed in a content analysis will produce a combination of linguistic context with the applied aspect of language translation. The patterns presented in the context of language focus on the address of the person who is the object of utterances and the application of the aspect of language translation is focused on the language technique of the summon context which has a neat effect on assessing the quality of the translation results.